A pragmatic multicentre randomised controlled trial comparing stapled haemorrhoidopexy with traditional excisional surgery for haemorrhoidal disease: the eTHoS study - Watson, A; Cook, J; Hudson, J; Kilonzo, M; Wood, J; Bruhn, H; Brown, S; Buckley, B; Curran, F; Jayne, F; Loudon, M; Rajagopal, R; et al. (NIHR Health Technology Assessment Programme, 2017)
Background Haemorrhoids are a benign ano-rectal condition and are highly prevalent in the population. Treatments involve clinic-based procedures and surgery. The surgical procedures available include stapled haemorrhoidopexy and traditional excisional haemorrhoidectomy and over 25,000 operations are performed for haemorrhoids annually in the United Kingdom. The disease is therefore both important to patients and to health service commissioners. Debate remains as to which of these surgical procedures are most clinically and cost effective. Objective The aim of this study was to compare the clinical and cost effectiveness of stapled haemorrhoidopexy (SH) and traditional excisional haemorrhoidectomy (TH). Design A large, open 2-arm parallel group pragmatic multicentre randomised controlled trial involving 32 United Kingdom hospitals and a within trial cost benefit analysis. A discrete choice experiment (DCE) was conducted to estimated benefits (willingness to pay). Participants Patients with grades II-IV haemorrhoids who had not previously undergone SH or TH were included in the study. Interventions Participants were randomised to either SH or TH. Randomisation was minimised, 1:1 according to baseline EQ-5D-3L, haemorrhoid grade, gender and centre via an automated system. Main outcome measures The primary outcome was area under the quality of life curve (AUC QoL) measured using the Euroqol-5D-3L (EQ-5D-3L) descriptive system over 24 months and the primary economic outcome was the incremental cost effectiveness ratio. Secondary outcomes included disease-specific QoL, recurrence, complications, further interventions and costs. Results Between January 2011 and August 2014, 777 patients were randomised (SH 389, TH 388). There was 774 participants included in the analysis due to one post-randomisation exclusion in SH arm and two in TH arm. SH was less painful than TH in the short term. Surgical complications were similar. EQ-5D-3L was higher for SH in the first 6 weeks after surgery but over 24 months the TH group had significantly better EQ-5D-3L scores; -0.073 95 % CI (-0.140,-0.006); p-value 0.0342. Symptoms and further interventions were significantly less in TH at 24 months. Continence was better in TH and tenesmus was less. The number of serious adverse events reported was 24/337 (7.1%) participants who received SH and 33/352 (9.4%) who received TH. There was two deaths in the SH arm both unrelated to the eTHoS study. Patient preference did not seem to influence the treatment difference. SH was dominated by TH as it cost more and was less effective. The net benefit for TH was higher than SH. Limitations Neither the participants, nor the assessors, were masked to treatment assignment and final recruitment was slightly short of the total target of 800. There was also substantial missing follow-up data. Conclusions While SH had less short-term pain, after 6 weeks, recurrence rates, symptoms, re-interventions and quality of life measures all favoured TH. In addition, TH is cheaper. As part of a tailored management plan for haemorrhoids, TH should be considered over SH as the surgical treatment of choice for haemorrhoids refractory to clinic based interventions. Future work Perform an updated meta-analysis incorporating recently conducted European trials (eTHoS, HubBLe, LingaLongo).